2006
DOI: 10.1007/s11910-006-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Update on huntington’s disease

Abstract: Huntington's disease (HD) is a devastating neurodegenerative disease causing progressive movement disorders, cognitive dysfunction, and behavioral changes. Since the causative mutation of an expanded polyglutamine repeat in the huntingtin gene was identified, significant progress has been achieved in elucidating pathogenic mechanisms. This review summarizes recent developments in evaluating the role of abnormal protein aggregation, transcriptional dysregulation, mitochondrial and bioenergetic dysfunction, exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…19,118,119 Although the results of 3 small DM clinical studies in ALS were negative, 68 -70 1 of these nevertheless showed a reduced decline in lower extremity function with DM. 68 Furthermore, these studies used subneuroprotective doses.…”
Section: General Conclusion and Research Agendamentioning
confidence: 99%
“…19,118,119 Although the results of 3 small DM clinical studies in ALS were negative, 68 -70 1 of these nevertheless showed a reduced decline in lower extremity function with DM. 68 Furthermore, these studies used subneuroprotective doses.…”
Section: General Conclusion and Research Agendamentioning
confidence: 99%
“…[3][4][5][6][7][8] Cellular toxicity in HD may involve interference of expanded Htt with gene transcription, vesicle transport, mitochondrial function, Ca 2+ homeostasis, and protein degradation machinery via proteasome or autophagy. [9][10][11][12][13][14][15] The nature of cytotoxic species of expanded Htt is unknown, but there is emerging evidence suggesting that they might be generated via Htt proteolysis. The main pathological feature of all CAG repeat disorders is the formation of nuclear and cytoplasmic inclusions in neurons of affected brain regions.…”
Section: Introductionmentioning
confidence: 99%